Depth-dependent effects of crop rotation and monoculture on dissolved organic matter quantity and quality - Ren, Tianjing; Debaene, Guillaume; Ukalska-Jaruga, Aleksandra; Smreczak, Bożena (Frontiers in Plant Science, 2025)
IntroductionSoil dissolved organic matter (DOM) regulates nutrient cycling and carbon sequestration, yet how cropping systems (rotation vs. monoculture) shape the vertical distribution and molecular traits of DOM remains unclear.MethodsWe leveraged a long-term experiment (est. 1994) at the IUNG-PIB Agricultural Experimental Station, Osiny, eastern Poland, comparing a three-year rotation (winter oilseed rapewinter wheatspring barley) with continuous winter wheat. Soils were sampled at 030, 3060, and 6090 cm. Cold-waterextractable DOM was quantified as dissolved organic carbon (DOC), nitrogen (DON), and phosphorus (DOP). UVVis metrics (SUVA280​, E4/E6) characterized molecular features, and environmental drivers were identified via variable-importance analysis.Results and discussionDOM concentrations declined with depth (P < 0.001). A management effect emerged only in the subsoil: DOC at 6090 cm was higher under monoculture than rotation (P < 0.05), indicating detectable but secondary cropping-system influences relative to depth controls. With depth, SUVA280​ increased and E4/E6 decreased consistently across systems, implying greater molecular weight and humification; thus, soil depth is the primary regulator of DOM molecular structure. Key drivers of DOM variability included soil organic carbon, total nitrogen, humus, available phosphorus, and depth. DOC variation was most associated with total nitrogen (14.92% contribution), total carbon (11.68%), and DOP (9.67%). DON was driven by DOC (17.64%), depth (16.00%), and available phosphorus (15.59%). DOP was shaped by humus (15.56%), total phosphorus (15.45%), and available phosphorus (15.43%). Collectively, these findings reveal pronounced depth-dependent differentiation of DOM quantity and traits in agricultural soils, with subsoil responses to management offering leverage points to optimize nutrient cycling and enhance long-term carbon storage.